The Efficiency of Alternative Punishments through the Prism of the Punitive System - Pântea, Andrei (Acta Universitatis Danubius. Juridica, 2024)
This study explores the role and impact of alternative penalties within the criminal justice system. It starts by defining alternative sanctions, including community service, and other forms, while examining the significance of these measures in supporting the social reintegration of offenders, often in combination with supplementary punishments. The research in question highlights the advantages of alternative punishments compared to custodial punishment, highlighting statistics on recidivism and the costs associated with different types of sanctions, through the lens of whether or not law enforcement agencies apply a harsher or milder punishment on a case-by-case basis case, in accordance with the purpose of the criminal penalty. It also looks at the challenges and limitations encountered in implementing these measures, including insufficient financial resources and public perception. Through international case studies, the research illustrates successful models of alternative sentencing and suggests possible improvements for the national system. The conclusion emphasizes the need for a balanced approach between punitive sanctions and reintegration measures, as well as the importance of education and professional training in the field of criminal justice. Overall, the present study argues for a reconsideration of the role of alternative punishments in the punitive system, arguing that they can significantly contribute to reducing recidivism and facilitating the social reintegration of criminals.